Undergraduate Students‘ Perceptions on Quillbot Paraphrasing Tool - Eka Fajar Rahmani (Scripta : English Department Journal, 2023)
The purpose is to investigate the students' perceptions of QuillBot utilization in writing class based on the framework of TAM 3. The problems include the students' perceptions of QuillBot in terms of usefulness, ease of use, and behavioral intention. The methodology is a descriptive study using a closed-ended questionnaire in the form of a Likert scale with five scales from strongly disagree to strongly agree. The questionnaire consists of 11 items covering three aspects: perceived usefulness, perceived ease of use, and behavioral intention to use QuillBot. The responses were then analyzed through a descriptive statistics framework, including frequency, percentage, and mean score. All aspects of TAM are perceived positively by the students. The perceived usefulness reaches 81.6%, categorized as positive perception, with a mean value of 4.26. The perceived ease of use reaches 90.75%, with a mean value of 4.34 categorized as strongly positive. The behavioral intention reaches 100% with a mean value of 4.82, categorized as strongly positive. This study has presented the result of an investigation of students'' perceptions of three aspects of TAM, including PU, PEU, and BI, towards QuillBot utilization. Therefore, QuillBot can be recommended as an alternative paraphrasing tool for EFL learners, especially in writing class.